Zinc levels and features of atopic dermatitis in children - T.V. Sorokman; N.O. Popely (Zdorovʹe Rebenka, 2020)
Background. Searching for the fundamental pathogenic mechanisms of atopic dermatitis (AD) and improvement of options for prevention and treatment, increasing attention is paid to the state of trace elements supply of the child’s body. Particular role is given to zinc, which is one of the most versatile trace elements. The purpose was to study the features of atopic dermatitis in children depending on the serum content of zinc. Materials and methods. The paper presents the materials of clinical observation, clinical laboratory and instrumental examination of 168 children aged 7 to 18 years with AD. The control group consisted of 60 healthy children. The serum zinc content was determined by atomic absorption spectroscopy on a C-115-M1 spectrophotometer according to the instructions that are attached to the device. Results. More than half of children (55.6 %) had very low levels of zinc (0.35 ± 0.11 mg/l), while another 22.2 % had extremely low levels (0.12 ± 0.02 mg/l). Several features of AD clinical course were noted: more frequent episodes of acute respiratory infection, predominance of moderate and severe course with periorbital, perioral, perianal dermatitis, dystrophic changes and hyperkeratosis of the nails, increased hair brittleness, expressed skin dryness (2.31 ± 0.73 vs. 1.92 ± 0.69 points, p < 0.01). High inverse correlation between serum zinc concentration and dry skin (p = 0.001; r = –0.67; t = –2.99), the value of the SCORAD index (p = 0.01; r = –0.49; t = –2.34) and the duration of the course of AD (p = 0.001; r = –0.46; t = –2.13). Significantly lower growth rates (p < 0.05) were found, especially significant growth retardation was found in children with very low zinc content (0.12 ± 0.02 mg/l). Conclusions. In children with atopic dermatitis, the plasma zinc content is probably lower than in healthy children. The children with low zinc content presented with some features of the clinical course of atopic dermatitis (more severe and prolonged course with periorbital and perianal localization, frequent respiratory infections, pronounced dystrophic changes of skin supplements, growth retardation).